2023
DOI: 10.3390/aerospace10070617
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Aerodynamic Performance of WIG Aircraft with a Micro-Vortex Generator (MVG) in Low-Speed Condition

Zinnyrah Methal,
Ahmad Syahin Abu Talib,
Mohd Supian Abu Bakar
et al.

Abstract: This present study investigated the potential of passive flow control to reduce induced drag by using a micro-vortex generator (MVG) at a backward-facing step (BFS) location. A wing-in-ground (WIG) craft is a fast watercraft that resembles a dynamically stabilised ship that can move or glide across the surface of water or land. Therefore, the wing of the WIG is designed to glide when in contact with water, which helps to decrease drag and enhance the lift of the overall vehicle. However, the existing design of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Zhadanov et al [20] studied VGs with three different shapes in a wind tunnel and found that they reduced drag coefficient and improved flight safety and quality compared to no VG treatment. Methal et al [27] tested ramp-type VGs on a watercraft used in aviation industries at different heights and angles ( • ) and found that 16 • and 0.6 δ, where δ is the boundary layer height, produced the least amount of drag coefficient over the watercraft's fuselage. None of these studies on aircraft wing modifications were designed to improve spray deposition and drift mitigation when agricultural aircraft conduct their routine spray applications.…”
Section: Introductionmentioning
confidence: 99%
“…Zhadanov et al [20] studied VGs with three different shapes in a wind tunnel and found that they reduced drag coefficient and improved flight safety and quality compared to no VG treatment. Methal et al [27] tested ramp-type VGs on a watercraft used in aviation industries at different heights and angles ( • ) and found that 16 • and 0.6 δ, where δ is the boundary layer height, produced the least amount of drag coefficient over the watercraft's fuselage. None of these studies on aircraft wing modifications were designed to improve spray deposition and drift mitigation when agricultural aircraft conduct their routine spray applications.…”
Section: Introductionmentioning
confidence: 99%